Finiteness and complementation patterns in Pazar Laz - Emgin, Betül. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study investigates the nature of (non-)finite clauses in Pazar Laz, a dialect of Laz language. Finiteness has been defined as a morpho-syntactic phenomenon which is associated with the presence of nominative case, tense (Chomsky, 1973), agreement (George&Kornfilt, 1981), and/or mood&modality (Aygen, 2001); as a pragmatic issue (Kalinina&Sumbatova, 2007); and as a structural phenomenon which ensures the presence of some syntactic levels (i.e. CP and TP etc. by Rizzi, 1997; Adger, 2007). The basic claim in this thesis is that Pazar Laz has developed a non-finite infinitival clause as a result of close contact with Turkish. Following this, we found out 4 types of complementation patterns with predicative core. These patterns include the structure which we claimed to be borrowed from Turkish. We looked at finiteness properties of these complementation patterns and tried to find out finiteness indicator in Pazar Laz. Following Adger (2007), we claimed that (non-) finiteness is determined via truncated levels including CP,TP,vP,VP; and clauses without CP and TP level can not be finite. Following this discussion, we found out that in Pazar Laz a fused T(ense) head is the main indicator of finiteness in Pazar Laz, and showed that tenseless clauses do not have CP and TP levels. An investigation of a borrowed infinitival clause in Pazar Laz led us to look at control issue in such a language (as there is not non-finite infinitival clauses in Caucasian languages following the discussion in Vamling, 1989). We found that in Pazar Laz there are not true control structures and the presence of agreement on the embedded verbal core shows the controller which is a pro. Finally, as an indirect indicator of finiteness, we find it necessary to analyze the nature of ergative case in Pazar Laz. Although there is one to one correspondence between the case and thematic role of the NPs/DPs, we showed evidence that ergative case is more like a structural case in Pazar Laz.
Keywords: Laz language.